Penggunaan Ordered Response Framework dalam Menentukan Faktor-Faktor Penentu Peringkat Utang Negara-Negara ASEAN+ - Agus Salim (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2022)
By using the Ordered Response Framework, this research studies the factors that determine the rating agencies in rating national debt, especially countries in the Southeast Asian region. The results obtained indicate that the model obtained with the Ordered Response Framework approach is quite good in determining the factors that determine the rating of the sovereign debt and in predicting levels and changes in ratings over time.